Consumer Credit Cooperatives as an Element of the Financial Market of Russia - V. Krivoshapova, Svetlana (2021)
One of the most important segments of the financial market is the credit market. Adequate and timely provision of the means necessary for production processes of economic entities, and the solution of vital tasks for the population largely depend on the possibility of obtaining credit resources. But the uneven distribution of financial and banking services, the supply of which is significantly behind demand for them, significantly inhibits the development of small businesses and causes imbalances in the economic and social development of the constituent entities of the Russian Federation.